1958
DOI: 10.1126/science.127.3303.876
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the 3-Methoxy Analog of Norepinephrine in Man

Abstract: Recent studies by Armstrong, McMillan, and Shaw(1) have shown that a major metabolite of norepinephrine and epinephrine found in human urine is 3-methoxy-4-hydroxymandelic acid. Subsequently it was shown by Axelrod (2) that the 3-hydroxy position of both norepinephrine and epinephrine can be methylated by animal tissues to yield the corresponding 3-methoxy analogs. The 3-methoxy analog of epinephrine (ME) was also reported to be present in rat urine (2). Since the conversion of catecholamines to their methoxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1959
1959
2014
2014

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The possibility that pheochromocytomas contain COMT and produce the O-methylated metabolites of catecholamines was first suggested by Sjoerdsma et al (1957), when these investigators isolated normetanephrine from tumor tissue and established the presence of the enzyme responsible for O-methylation. Three years later, Kopin and Axelrod (1960) confirmed that pheochromocytomas contain high concentrations of metanephrine and MHPG.…”
Section: Catecholamine-producing Tumorsmentioning
confidence: 99%
“…The possibility that pheochromocytomas contain COMT and produce the O-methylated metabolites of catecholamines was first suggested by Sjoerdsma et al (1957), when these investigators isolated normetanephrine from tumor tissue and established the presence of the enzyme responsible for O-methylation. Three years later, Kopin and Axelrod (1960) confirmed that pheochromocytomas contain high concentrations of metanephrine and MHPG.…”
Section: Catecholamine-producing Tumorsmentioning
confidence: 99%
“…Increased excretion of NM, the only other NE metabolite believed to occur in urine in large quantities (6,13), has also been suggested as a possible means of diagnosing pheochromocytoma (6). Up to this time, however, the procedures for demonstrating NM and WI in urine have been inadequate for routine use (14).…”
Section: Resultsmentioning
confidence: 99%
“…The possibility that pheochromocytomas contain COMT and produce the Omethylated metabolites of catecholamines was suggested by Sjoerdsma et al (1957), when these investigators isolated NMN from tumor tissue and established the presence of the enzyme responsible for O-methylation. Three years later, Kopin and Axelrod (1960b) confirmed that pheochromocytomas contain high concentrations of MN and MHPG.…”
Section: Catechol-o-methyltransferase and The Diagnosis Of Pheochromomentioning
confidence: 97%